2022
DOI: 10.1038/s41551-022-00951-w
|View full text |Cite
|
Sign up to set email alerts
|

Graph deep learning for the characterization of tumour microenvironments from spatial protein profiles in tissue specimens

Abstract: Multiplexed immunofluorescence imaging enables high-dimensional molecular profiling at subcellular resolution. However, learning disease-relevant cellular environments from these rich imaging data is an open challenge. We developed SPAtial CEllular Graphical Modeling (SPACE-GM), a geometric deep learning framework that flexibly models tumor microenvironments (TMEs) as cellular graphs. We applied SPACE-GM to 658 head-and-neck and colorectal human cancer samples assayed with 40-plex immunofluorescence imaging to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 44 publications
1
49
0
Order By: Relevance
“…Graph attention 12 and other graph kernels with more degrees of freedom may be more sensitive to complex tissue niche motives. Second, pooling across the graph may be performed globally or hierarchically, as previously also discussed by Wu et al 5 . Aggregation of information across a graph becomes even more relevant if larger graphs are considered, which may for example become available in the context of tissue clearing 13 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Graph attention 12 and other graph kernels with more degrees of freedom may be more sensitive to complex tissue niche motives. Second, pooling across the graph may be performed globally or hierarchically, as previously also discussed by Wu et al 5 . Aggregation of information across a graph becomes even more relevant if larger graphs are considered, which may for example become available in the context of tissue clearing 13 .…”
Section: Discussionmentioning
confidence: 99%
“…3a-d). It was previously reported that the spatial distribution of immune cells in colorectal cancer is predictive of disease outcome and is used to stratify tumors 5,10 . Indeed, we found that an MLP trained on an immune cell dispersion estimate per image was more predictive of tumor class in test images of colorectal cancer than the baseline pseudo-bulk model that only reflects composition but not architecture (Fig.…”
Section: Predictive Features Of Tumor Architecture Are Defined By An ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Since this approach focuses directly on pixel-level information instead of reconstruction from single-cell data, it can identify both extracellular structures and cellular communities over a range of microto macro-scale. Pixel-based analysis also forms the basis of modern artificial intelligence learning from imaging, and thus paves the way for more complex learning algorithms to be applied to multiplex tissue data (10, 45,61). Various methods are currently available for pixel-based spatial domain detection from ST data (8, 55,63).…”
Section: Introductionmentioning
confidence: 99%